2017
DOI: 10.1111/tct.12706
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence teaching in UK medical schools: a cross-sectional study

Abstract: SUMMARYBackground: Domestic violence and abuse (DVA) is a leading contributor to the physical and mental ill health of women. Recent international guidance recommends that undergraduate medical curricula should include DVA. We do not know what is currently taught about DVA to medical students in the UK. Method: Teaching leads from all UK medical schools (n = 34) were invited to participate in an 18-item online survey about what DVA education is provided, their views of this provision and any feedback provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 7 publications
4
22
0
1
Order By: Relevance
“…There are of course barriers for the victims to overcome to report IPV and the importance of gaining trust and encouraging these women to seek help cannot be overemphasized. A research done in UK regarding formal teaching about domestic violence and abuse in medical schools revealed that the education was not adequate [5]. Without doubt all medical school should in their medical curriculum include a thorough formal teaching on IPV, how to detect and how to support and know what resources are available to assist the victims.…”
mentioning
confidence: 99%
“…There are of course barriers for the victims to overcome to report IPV and the importance of gaining trust and encouraging these women to seek help cannot be overemphasized. A research done in UK regarding formal teaching about domestic violence and abuse in medical schools revealed that the education was not adequate [5]. Without doubt all medical school should in their medical curriculum include a thorough formal teaching on IPV, how to detect and how to support and know what resources are available to assist the victims.…”
mentioning
confidence: 99%
“…However, of these, 11 reported providing zero to two contact hours on the subject over a five-year degree. Three quarters felt provision of domestic violence and abuse teaching was inadequate or not enough [32]. Similar audits are needed on domestic violence and abuse teaching on UK nursing and other healthcare professional curricula.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in several countries have evidenced the positive influence of professional training on the violence phenomenon, showing the need for the themes' inclusion in undergraduate courses, based on content that addresses violence (Bonfim 2015, Potter & Feder 2018Bravo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%